Comparison and performance study of different I/Q imbalance and channel compensation schemes for OFDM receivers - Haq, K.; Chung, Kah-Seng (IEEE Computer Society, 2015)
This paper presents an adaptive combined correction and compensation (ACCC) scheme to mitigate the distortion caused by I/Q imbalance and multipath channel, for OFDM receivers. For the proposed scheme, the estimation of the I/Q and channel parameters have been performed in the frequency domain. By the help of the estimated values, a nominal I/Q gain and phase has been obtained which has been fed back to do the I/Q correction in the time domain. The corrected signal with some residue I/Q imbalance along with the channel have been compensated afterwards. The performance of the proposed scheme has been extensively studied by means of computer simulations using MATLAB. With the proposed ACCC scheme, the signal to noise ratio (SNR) degradation is approximately 2 dB higher than the reference symbol error rate (SER) obtained for no I/Q imbalance and channel condition, at a specified symbol error rate (SER) of 10-3. Next, in order to assess the robustness of the proposed scheme, it has been compared with three other previously published schemes, under different conditions. The results depict that the proposed ACCC scheme significantly outperforms the three other existing schemes by expending less than 2% of the subcarriers as pilots.